Pengujian Black Box pada Aplikasi Sistem Seleksi Pemenang Tender Menggunakan Teknik Equivalence Partitions - Aini Arifta Arwaz; Theja Kusumawijaya; Rediansyah Putra; Kurnia Putra; Aries Saifudin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
The tender winner selection system is important to ensure the winner will complete the project well. If there is a selection error that caused the project to fail, the application must be tested and error free. Testing in this study uses Black Box Testing. The Black Box Testing Method consists of several methods including Equivalence Partitions, Boundary Value Analysis, Comparison Testing, Sample Testing, Robustness Tesing, and others. Among the many methods of testing, in this study the method of testing Equivalence Partitions was chosen. The purpose of the Equivalence Partitions method is to look for errors in functions that are wrong or missing, errors in the interface, errors in data structures or database access, performance errors, initialization errors and final destinations. Based on the test results show there are still many shortcomings when validating data to be entered, so that it can cause data stored in the database does not match the expected data.